PEMBERIAN PUPUK ORGANIK SEBAGAI CAMPURAN MEDIA TUMBUH BABY KAILAN (Brassica oleracea L.) UNTUK TIGA KALI PENANAMAN SECARA VERTIKULTUR - Sheibila Naqi Alfadillah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The research aims to determine the effect of the addition of some organic fertilizers as mixed growing medium for growth and yield of baby kailan and get the best type of organic fertilizer to support the growth and yield of babykailan plants for three times planting in verticulture. The research was carried out at the Kebun Percobaan of the Agriculture Faculty, Universitas Riau. The research lasted for four months starting from February to May 2019 and in experimentally that consisting of four treatments and arranged using a completely randomized block design (RBD) of organic fertilizer consisting of: Cow manure, Goat manure, Chicken manure, and Oil Palm Empty Fruit Bunches (OPEFB) compost. The observed parameters were plant height (cm), number of leaves (strands), fresh weight per plant (g), plant weight for consumption per plant (g), and root volume (ml). The observational data were analyzed using the Statistical Analysis System (SAS) program. The results showed that the OPEFB compost treatment provided the best for growth and yield of babykailan in the first, second and third planting. The addition of chicken manure and cow manure as mixed growing medium for baby kailan increased growth and crop yields until the third planting compared to the first planting but higher growth and yields were shown by the addition of OPEFB compost.OPEFB compost gave the best results for three plantings for plant production parameters, namely number of leaves 19,81 leaves, fresh weight per plant71,93 g and plant weight for consumption per plant 65,09 g.Keywords:verticulture, babykailan, organic fertilizer